Pengaruh Orientasi Pasar, Inovasi, Keunggulan Bersaing terhadap Kepuasan Pelanggan UMKM Kuliner Tangerang dengan Mediasi Teknologi - Kunti Hayu Kartiko; Imas Sukaesih; Bagus Manunggal (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to evaluate the impact of market orientation, innovation, and competitive advantage on customer satisfaction of culinary MSMEs in Tangerang City, where technology acts as a mediating variable. The background of this study comes from the increasingly fierce competition faced by MSMEs in the digital era and the urgency of an adaptive marketing strategy that relies on technology to maintain customer satisfaction. The methodology used is a quantitative approach with SEM analysis techniques through Smartpls software. A total of 190 respondents who are satisfied customers of culinary MSMEs in Tangerang City became the sample of this study. The findings of this study indicate that market orientation, innovation, and competitive advantage have a significant influence on technology adoption, and affect both directly and indirectly on customer satisfaction with the mediating role of technology. These results confirm that technology adoption is a vital element in improving service quality and customer satisfaction. This research also offers practical insights for businesses to maximize technology-based strategies.